The vibe of skating; design and testing of a vibro-tactile feedback system - Jansen, A. J.; Dekker, M.; van der Steen, D. (Proceedings, 2018)
Providing athletes with real-time feedback on their performance is becoming common in many sports, also in speed skating. This research-by-design project aims at finding a tool that allows the speed skater to get real-time feedback on his performance. Speed skaters often mention a so-called "good feeling" when skating behind a better skater. It is the feeling nearly every speed skater is after when skating alone; skate with less power while maintaining the same speed and feeling of ease. A longer push-off phase at a constant cadence has proven to contribute to this ideal situation but is hard for the coach alone to influence this. Therefore, a system was designed that measures the skating cadence and challenges the skater to change his skating stroke by means of vibro-tactile feedback. Four subjects have tested the feedback system. From this test, we concluded that the system provides meaningful feedback towards changing the skating cycle.